A Study on Co-morbidities, Precipitating and Associated Factors of Nocturia among Adults-Pilot Study (International Journal of Nursing Education, 2019)
Introduction: Night urination is an extremely niggling condition affecting men and women of all ages. Multiple medical conditions are associated with nocturia and negatively impact the quality of life. However people often hesitate to seek the healthcare and consider as an untreatable condition and part of aging process. Understanding the underline illness and its associated factors are vital aspects in the management of Nocturia. Objectives: The aim of this study was to assess the Co-morbidity, Precipitating and associated factors of Nocturia among adults. Materials and Method: An exploratory descriptive design was carried out among 54 adult clients of 35-65 years of age. The data was collected using self-assessment tool of Co-morbidity, Precipitating and associated factors of Nocturia and interview technique was adopted. The data was analysed using descriptive and inferential statistics. Results: The finding of the study showed that the Proportion of Nocturia among adult clients was 54%. More than half 58.6% of the subjects were males and the mean age 55.4±8.8. The highest respondents were with primary education. The Majority of the respondents( 96.6%) were married. The severity of Nocturia assessment shows 48.3% had moderate form of nocturia. The Co-morbidity assessment reveals that the 35% of subjects equally had increased blood pressure and constipation and 21% of subjects equally had Diabetes Mellitus and incontinence of urine. Among 12 females 25% of subjects had uterus related diseases and among 17 males, 35% of subjects had disease related to prostate gland. The results related to Precipitating factors of Nocturia shows that 38 % of subjects were consuming coffee, 28% were smokers, and 69% were taking Afternoon Naps, 97 % were consuming more water / fluids before bedtime, 93% were getting anxious easily, 90% were consuming spicy foods, 87% were urinating before going bed. The Associated factors of Nocturia result shows 100% of the subjects had insomnia, 55% had frightening or unpleasant dream during sleep, and 41% were reported that they snore. The study found that there was significant association between the Co-morbidity of Nocturia and the selected demographic variables such as age (p?0.043), Marital status(p?0.001) ,number of children (p?0.013) , occupation (p?0.001), Diet (p?0.001), BMI (p?0.001), Type of attainment of menopause (p?0.003) and Type of delivery(p?0.003) . Conclusion: The study found that numerous factors contribute to the night urination